Speech nasality and nasometry in cleft lip and palate - Larangeira,Fabiane Rodrigues (2016)
ABSTRACT INTRODUCTION: Perceptual evaluation is considered the gold standard to evaluate speech nasality. Several procedures are used to collect and analyze perceptual data, which makes it susceptible to errors. Therefore, there has been an increasing desire to find methods that can improve the assessment. OBJECTIVE: To describe and compare the results of speech nasality obtained by assessments of live speech, the Test of Hypernasality (THYPER), assessments of audio recorded speech, and nasometry. METHODS: A retrospective study consisting of 331 patients with operated unilateral cleft lip and palate. Speech nasality was assessed by four methods of assessment: live perceptual judgement, THYPER, audio-recorded speech sample judgement by multiple judges, and nasometry. All data were collected from medical records of patients, with the exception of the speech sample recording assessment, which was carried out by multiple judges. RESULTS: The results showed that the highest percentages of absence of hypernasality were obtained from judgements performed live and from the THYPER, with equal results between them (79%). Lower percentages were obtained from the recordings by judges (66%) and from nasometry (57%). CONCLUSION: The best results among the four speech nasality evaluation methods were obtained for the ones performed live (live nasality judgement by a speech pathologist and THYPER).